PEMBERDAYAAN LANSIA SURABAYA MELALUI AKTIVITAS KOGNITIF DAN AKTIVITAS SOSIALSEBAGAI UPAYA MENGATASI KONDISI FISIK DAN PSIKOLOGISNindria Untarini Fakultas Ekonomi, Uiversitas Negeri Surabaya (Lentera, Jurnal Studi Perempuan, 2013)
Abstract The aim of this research is to identify the physical and psychological problems face by female elderly, and the solutions to overcome the problems through cognitive and social activities. The cognitive activities include the activity of painting and art skills. While, the social act is participating in “Karang Weda Paguyuban”. The research targets are thirty female elderly who participate in “Karang Wreda Barata Jaya RW VSurabaya”. The data collection is done by using several techniques such as observation,  interview, and questionnaire The data were analyzed using descriptive qualitative with percentage technique. The finding shows that the activities of painting and creativity can train physical and cognitive organs. While social activities in “paguyuban” become the media of sharing ideas, experiences, and affections. These activities help them to cope with psychological problems and help them to achieve the maximum quality of life.Keywords: elderly needs, physical deterioration, brain decline, elderly empowerment, training.